Platelet Measurements and Type 2 Diabetes: Investigations in Two Population-Based Cohorts - Rodriguez, Benjamin A. T.; Johnson, Andrew D. (Frontiers in Cardiovascular Medicine, 2020)
Type 2 diabetes is a major risk factor for cardiovascular disease. Given the contribution of platelets to atherothrombosis—which in turn is a major contributor to cardiac events, there may be cause to consider platelet function in management of diabetes. Despite the large body of research concerning the role of platelets in cardiovascular complications of type 2 diabetes, evidence from population-based studies of platelet aggregation in diabetes is limited. Mean Platelet Volume (MPV), a cell trait partially associated with markers of platelet activity, is more commonly available. We investigated the association of metabolic syndrome and diabetes with platelet aggregation to three physiological agonists, ADP, collagen, and epinephrine, in the Framingham Heart Study Offspring cohort. We further examined the relationship between MPV measured with Beckman Coulter LH750 instruments and self-reported diabetes as well as MPV and diabetes medication in the UK BioBank cohort, performing the largest such analysis to date. Increased platelet aggregation associated with prevalent diabetes was observed for low concentration epinephrine (0.1 μM) alone and only in analyses of participants stratified either by male sex and/or having metabolic syndrome. Other agonists and concentrations were not significant for prevalent diabetes, or in opposite direction to the main hypothesis (i.e., they showed lower platelet aggregation associated with diabetes). After a median of 18.1 years follow-up, no platelet aggregation trait was associated with increased risk of diabetes (n = 344 cases). As expected, increased MPV was significantly associated with diabetes (β = 0.0976; P = 8.62 × 10−33). Interestingly, sex-stratified analyses indicated the association of MPV with diabetes is markedly stronger in males (β = 0.1232; P = 1.00 × 10−31) than females (β = 0.0514; P = 7.37 × 10−5). Among diabetes medications increased MPV was associated with Insulin (β = 0.1341; P = 1.38 × 10−11) and decreased MPV with both Metformin (β = 0.0763; P = 1.99 × 10−6) as well as the sulphonylureas (β = 0.0559; P = 0.0034). Each drug showed the same direction of effect in both sexes, however, the association with MPV was nearly twice as great or more in women compared to men. In conclusion, platelet function as measured by aggregation to ADP, collagen, or epinephrine does not appear to be consistently associated with diabetes, however, MPV is robustly associated suggesting future work may focus on how MPV segments pre-diabetics and diabetics for risk prediction.